(untitled) (Global Journal of Management and Business Research, 2016)
The objective of this paper is to reflect on the relationship between conservatism as a state of mind and the international performance of family businesses. To achieve this, we opted for a dialectical approach associated with a narrative synthesis. Thus, two theses were highlighted. The first considers conservatism as a factor inhibiting internationalization. Because of their emotional attachment to the business and the stability of property, family businesses generally show a greater reduction in their innovativeness and their proactive than non-family businesses. The second theory considers conservatism as neutral or sometimes challenging internationalization. Great importance was given to the complex social resources which are the product of interactions between family members, and which are likely to ensure greater international performance.